2015
DOI: 10.1177/2373379915594391
|View full text |Cite
|
Sign up to set email alerts
|

Experiential Learning in Kinesiology

Abstract: Overview Service learning is a form of experiential learning that pairs academic educational experiences and community organizations to promote training, civic engagement, and meaningful service by students to their community. Kinesiology programs have moved toward increasing experiential and service learning options in health promotion for their students, but few have evaluated the student perceptions of these programs. Purpose The purpose of the current study was to conduct a qualitative evaluation of a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 17 publications
1
28
0
Order By: Relevance
“…Within a traditional classroom setting, addressing tangible societal issues with faith integration may be challenging. However, engaging students in service and partnership encourages realistic practice and reflection on experiences (de Groot, Alexander, Culp, & Keith, 2015). Creatively pursuing community engagement can enhance student learning and provide an opportunity for authentically exploring faith as students learn with and from community partners.…”
Section: Community-based Learning Pedagogymentioning
confidence: 99%
“…Within a traditional classroom setting, addressing tangible societal issues with faith integration may be challenging. However, engaging students in service and partnership encourages realistic practice and reflection on experiences (de Groot, Alexander, Culp, & Keith, 2015). Creatively pursuing community engagement can enhance student learning and provide an opportunity for authentically exploring faith as students learn with and from community partners.…”
Section: Community-based Learning Pedagogymentioning
confidence: 99%
“…According to Rogers [3], experiential learning refers to an active learning approach that allows trainees to use and critically process knowledge, skills, abilities (KSAs), and experience gain via the educational process. Previous studies examining learning in a wide array of disciplines found that experiential learning effectively leads to better learning results [4][5][6][7]. Service learning (SL), a form of experiential learning [8], is designed to foster a collaboration between students and community or health organization(s) to provide an opportunity to eventually apply learned KSAs to meet the needs of a specific community [9].…”
Section: Introductionmentioning
confidence: 99%
“…Service learning (SL), a form of experiential learning [8], is designed to foster a collaboration between students and community or health organization(s) to provide an opportunity to eventually apply learned KSAs to meet the needs of a specific community [9]. Researchers from several studies examining SL programs in kinesiology have documented the benefits of students' participation, including enhanced levels of self-efficacy [10], moral development [11], deeper understanding of course contents [7], and greater interaction with culturally different individuals [12]. Accordingly, SL within the discipline of kinesiology could deliver an exercise intervention to community firefighters who are hypertensive and overweight.…”
Section: Introductionmentioning
confidence: 99%
“…The promotion of student experiences in education was thus perceived as a means to enhance students’ capacity to participate in democracy (Kolb, 1984). In the present day, the prioritization of experiential learning in professional education is particularly evident among health professions, with many health professions, such as medicine, nursing, pharmacy, exercise science, and public health, requiring their preprofessionals to engage in internships, practica, fieldwork, or clinical rotations (Brown, Heaton, & Wall, 2007; Gregorio, DeChello, & Segal, 2008; de Groot, Alexander, Culp, & Keith, 2015; Meurer et al, 2011; Montgomery & Johnson, 2015).…”
mentioning
confidence: 99%